2018
DOI: 10.1042/bsr20180475
|View full text |Cite
|
Sign up to set email alerts
|

ZFAS1 functions as an oncogenic long non-coding RNA in bladder cancer

Abstract: Long non-coding RNA (lncRNA) ZFAS1 (zinc finger antisense 1) has been suggested to have an oncogenic role in the tumorigenesis of human malignant tumors. However, the expression status and biological function of ZFAS1 in bladder cancer is still unknown. Thus, the purpose of the present study is to explore the clinical value of ZFAS1 in bladder cancer patients, and the biological function of ZFAS1 in bladder cancer cell. In the present study, we found ZFAS1 expression was increased in bladder cancer tissues com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 35 publications
1
18
0
Order By: Relevance
“…[10][11][12] For instance, lncRNA ZFAS1 has been found as an oncogene in bladder cancer. 13 Lymphoid enhancer-binding factor 1 antisense RNA 1 (LEF1-AS1), is a newfound lncRNA that locates in chromosome 4q25, which was firstly found to be upregulated and predict prognosis in colorectal cancer (CRC) 14 and further revealed to promote malignancy in glioblastoma. 15 However, it remains obscure whether LEF1-AS1 implicates in OSCC.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] For instance, lncRNA ZFAS1 has been found as an oncogene in bladder cancer. 13 Lymphoid enhancer-binding factor 1 antisense RNA 1 (LEF1-AS1), is a newfound lncRNA that locates in chromosome 4q25, which was firstly found to be upregulated and predict prognosis in colorectal cancer (CRC) 14 and further revealed to promote malignancy in glioblastoma. 15 However, it remains obscure whether LEF1-AS1 implicates in OSCC.…”
Section: Introductionmentioning
confidence: 99%
“…The lncRNA ZFAS1, which is at located at 20q13, has been found stably expressed in many kinds of tumors [13]. Increasing evidence has shown that ZFAS1 is upregulated and involved in occurrence and development of several tumors, such as bladder cancer [14], cervical cancer [15], prostate cancer [16], and breast cancer [17]. Many studies have also shown that ZFAS1 serves as an oncogene in cancers, which could promote cell proliferation and invasion and inhibit cell apoptosis via regulating downstream protein expression [18].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, LncRNA-MALAT-1, which is highly expressed in bladder transitional cell carcinoma (BTCC), was found to play an important role in tumorigenesis and metastasis of BTCC, and the upregulation of MALAT1 were positively associated with advanced clinical and pathological stage and shorter survival of BTCC patients [7]. lncRNA-ZFAS1 (zinc finger antisense 1) was overexpressed in bladder cancer, and knockdown of ZFAS1 represses bladder cancer cell proliferation by upregulating the expression of KLF2 and NKD2, and inhibiting cell migration and invasion by downregulating ZEB1 and ZEB2 expression [8]. Thus, various lncRNAs were reported to be involved in carcinogenesis.…”
Section: Introductionmentioning
confidence: 99%